Pengembangan Penuntun Praktikum Disertai Gambar Pada Materi Sel Untuk Kelas XI Sekolah Menengah Atas - Riza, Elda; Sumarmin, Ramadhan; Sari, Liza Yulia (STKIP PGRI Sumbar, 2013)
ABSTRACTPractical requires students to be able to work in the lab or in the field. By carrying out their practical acquire knowledge, understanding, and behavioral aspects of the other, and to develop the skills to live in society meaningfull. In addition, the students will find themselves contribute to arouse their interest and enthusiasm for learning. Implementation of practical activities in schools need practical guidance so that students more easily understand the material that will be practicalled. However, at school SMAN 1 Lembah Melimtang students conducting lab does not have specific guidelines or guiding practical. Accordingly, the research aimed to result a valid and practical guidance practical. This study is using a three-stage development of the 4-D models, the stage define, stage design , and development stage (develope). Test subjects were students of class XI Science SMAN 1 Lembah Melintang, amounting to 30 people. The data of this study is primary data taken from validity and practicalities are then analyzed with descriptive analysis. Practicalities by teachers who are included in a very practical and practicalities criteria by 87.85% students with practical category. It can be conclude has produced valid and practic a guide with pictures on a cells material for class XI SMA.